2013
DOI: 10.1117/12.2025099
|View full text |Cite
|
Sign up to set email alerts
|

Tilted exposure microsphere nanolithography for high-throughput and mask-less fabrication of plasmonic molecules

Abstract: Fabrication of nanostructures for applications such as plasmonics and metamaterials are typically accompanied by a slow production and limited area due to the required sub-micron feature sizes. In these applications, periodic array of metal/dielectric features can produce optical resonance responses such as optical field enhancement response, Fano response, chiral response, and negative refractive index. Here, we propose a mask-less photolithography technique that can produce a variety of periodic nanostructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fig. 4c and e, respectively [88]. Recently, it was shown that tilted exposure could also be carried out in DUV projection SLPL technique by inducing the formation of a photonic nanojet with different angles of incidence [87].…”
Section: Tilted Exposurementioning
confidence: 95%
See 1 more Smart Citation
“…Fig. 4c and e, respectively [88]. Recently, it was shown that tilted exposure could also be carried out in DUV projection SLPL technique by inducing the formation of a photonic nanojet with different angles of incidence [87].…”
Section: Tilted Exposurementioning
confidence: 95%
“…This approach is actually a derivative of the conventional SLPL. Mohseni et al [88] demonstrated the capabilities of this method in producing an array of complex plasmonic molecules over a large area. The classical schematic of the fabrication process is illustrated in Fig.…”
Section: Tilted Exposurementioning
confidence: 99%